Impact of nitrogen and phosphorus fertilizer on growth and yield of bambara groundnut - Hasan, Muhammad Mahmudul; Uddin, Md. Kamal; Mohamad, Mahmud Tengku Muda; Tan, Ali Kee Zuan; Motmainna (Plant Archives, 2019)
Bambara groundnut (Vigna subterranea) is an indigenous African crop which belongs to the family fabacea and sub-family of faboidea. It seeds contain 63% carbohydrate, 19% protein and 6.5% oil and good source of fibre, calcium, iron and potassium. Hence, this study aimed to determine the effect of nitrogen (N) and phosphorus (P) on growth and yield bambara groundnut. A pot experiments was conducted in ladang 15 at the Faculty of Agriculture; Universiti Putra Malaysia. The experiment was performed Randomized Complete Block Design (RCBD). The size of the pot was 65.94 cm2. The experiment was conducted in a factorial design with four levels of N (0, 10, 20, 30 kg/ha) and P (0, 20, 40 and 60 kg/ha). In this study, N and P fertilizer was played dominating role for vegetative growth of the plant. Plant height (20.65 cm), leaves number (262), leaf area (2140.54 cm2), number of pod (47.25) and pod weight (22.8 g) increased with the application of level of N and P. Vegetative growth and yield of the plant was better at N30P60 kg/ha than the all other treatments. It can be concluded that by using N30P60 kg/ha growth and yield of bambara groundnut is maximum.